VICE OF INITIATIVE AND LEGISLATIVE POWER IN THE FEDERAL DISTRICT: POLITICS IN THE APPROPRIATION OF LEGISLATIVE AGENDAS - de Menezes Júnior, Gilson Aires (Seven Editora, 2025)
The phenomenon of appropriation of the agenda can have great consequences for the effectiveness of citizens' rights, by affecting the effectiveness and credibility of legislative action. In this vein, the articulation between the Legislative and Executive branches seems to show signs of validation of propositions with a flagrant defect of unconstitutionality, whether at the stage of the processing of the proposal or at the time of the veto of the Executive branch. This article, prepared with the aim of analyzing theoretical and practical issues of the Legislative power of the Federal District, will address the verification of this phenomenon, analyzing its causes, effects and consequences, as a way to broaden the debate.DOI: https://doi.org/10.56238/sevened2024.037-187